2014
DOI: 10.1111/ejn.12799
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic vesicle glycoprotein 2A modulates vesicular release and calcium channel function at peripheral sympathetic synapses

Abstract: Synaptic vesicle glycoprotein (SV)2A is a transmembrane protein found in secretory vesicles and is critical for Ca(2+) -dependent exocytosis in central neurons, although its mechanism of action remains uncertain. Previous studies have proposed, variously, a role of SV2 in the maintenance and formation of the readily releasable pool (RRP) or in the regulation of Ca(2+) responsiveness of primed vesicles. Such previous studies have typically used genetic approaches to ablate SV2 levels; here, we used a strategy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…SV2A is the most ubiquitous and is expressed as a transmembrane glycoprotein in secretory vesicles on presynaptic terminals. It is critical to synaptic function, particularly Ca2+-dependent exocytosis [86], and is known to be the binding site of levetiracetam [87].…”
Section: Sv2a Petmentioning
confidence: 99%
“…SV2A is the most ubiquitous and is expressed as a transmembrane glycoprotein in secretory vesicles on presynaptic terminals. It is critical to synaptic function, particularly Ca2+-dependent exocytosis [86], and is known to be the binding site of levetiracetam [87].…”
Section: Sv2a Petmentioning
confidence: 99%
“…(3) naive to PD treatment at baseline; (4) did not fulfill the diagnostic criteria for PD mild cognitive impairment, 33 dementia, 34 or depression 35 ); (5) no history of other neurological or psychiatric disorders; and (6) no contraindication to MRI. Healthy controls had no history of neurological or psychiatric disorders.…”
Section: Participant Demographicsmentioning
confidence: 99%
“…Synaptic vesicle protein 2A (SV2A) is a transmembrane protein widely expressed in presynaptic terminals throughout the brain, where it regulates neurotransmission. 4,5 Neurons lacking SV2A demonstrate impaired ability of vesicles to fuse with the plasma membrane. 6 There are several lines of evidence suggesting that accumulation of α-synuclein in presynaptic terminals impairs synaptic proteins, synaptic plasticity, and neurotransmission and subsequently induces axonal damage and impairment of intracellular trafficking.…”
mentioning
confidence: 99%
“…Levetiracetam has a clear and distinct mechanism of action; it acts on the SV2A integral membrane glycoprotein present on all synaptic vesicles ( Lynch et al, 2004 ). Recent work by Vogl et al (2015) in superior cervical ganglion neurons demonstrated that SV2A maintained normal neurotransmission by regulating readily releasable pool size, had a facilitatory role in recovery from synaptic depression, and impaired presynaptic voltage-dependent Ca 2+ channel current density. Specific details on the mechanisms of action of AEDs at the level of receptors and ion channels have been extensively reviewed ( Kwan et al, 2001 ; Löscher et al, 2013 ; Moshé et al, 2015 ).…”
Section: Neurobiology and Psychopharmacology Of Epilepsy And Aggrmentioning
confidence: 99%